Iraqi Registry Data Proves Safety and Efficacy of switching to Adalimumab Biosimilar in Treating Rheumatoid Arthritis - Abbas, Yasameen; Ihsan, Nabaa; Adnan, Asal; Moayad, Marwa; AlKazzaz, Ali; Maroof, Avin; Abdulrahman , Ali; Abdulateef, Nazar; AlOsami, Mohammad; Gorial, Faiq; Altahhan, Mohammed; Almansi, Zahraa; et al. (AL-Kindy College Medical Journal, 2024)
Background: Adalimumab is approved for Rheumatoid Arthritis (RA). In 2021, A biosimilar (ABP501;Amgevita®) was licensed in Iraq. The current study aimed to ensure safety and Efficacy of Amgevita in RA Patients in Iraq. Patients and Methods: A Cross sectional Observational study Started on 69 RA Records receiving Amgevita. Data collected from local registry then examined for disease activity and adverse reactions for 9 months follow up. Results: Thirty patients completed the 9 months period of the study: aged (49±14) years; 77.5% females. After 3, 6 and 9 months of follow up, patients’ mean (SD) CDAI 27.8 ( 13.60 ) which was statistically lower (19.80) (6.96), 17.70 (2.790), and 19 (1.040), p<0.001. With a mean change of CDAI: 8 (p<0.001), 10.1 (p<0.001), and 8.78 (p<0.001) after 3, 6, and 9 months. Cumulative percentage of responders was 55.00% and Cumulative percentage of probability of change of disease activity was 86.00%, No patient achieved remission and no significant Side effects recorded. In conclusion Amgevita is Effective and Safe in RA.